2020
DOI: 10.1109/access.2020.2971544
|View full text |Cite
|
Sign up to set email alerts
|

Cooperate Delegation of Computation for Rational Party Using Zero-Determinant Strategy Approach

Abstract: Delegating calculation is an important approach to solve the correctness and reliability of task subcontracting and delegating calculation results in cloud computing environment. However, the dynamic, complexity and openness of cloud computing bring unprecedented risks to the security and reliability of computing tasks. To solve the problem the new approach is presented. Firstly, the game theory is introduced into the delegating calculation, and the single-client and multi-server rational delegating calculatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Furthermore, the control ability of ZD strategies has also been extended [19], [20], [21]. As application studies, ZD strategies have been applied to several problems in the field of information and communications technology, such as resource sharing in wireless networks [22], [23], mining in blockchain [24], crowdsourcing [25], the Internet of Things [26], cloud computing [27], and data trading [28]. In terms of unbeatable strategies, the author proved that the unbeatable TFT is a ZD strategy in two-player symmetric games [29].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the control ability of ZD strategies has also been extended [19], [20], [21]. As application studies, ZD strategies have been applied to several problems in the field of information and communications technology, such as resource sharing in wireless networks [22], [23], mining in blockchain [24], crowdsourcing [25], the Internet of Things [26], cloud computing [27], and data trading [28]. In terms of unbeatable strategies, the author proved that the unbeatable TFT is a ZD strategy in two-player symmetric games [29].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from these theoretical studies on general properties of ZD strategies, there are many applications of ZD strategies. In the field of information and communications technology, ZD strategies have been applied in resource sharing in wireless networks [27,28], smart grid systems [29], mining in blockchain [30,31], crowdsourcing [32,33], mobile crowdsensing [34], the Internet of Things [35], cloud computing [36], federated learning [37], and data trading [38], in order to unilaterally realize some favorable states. Another field of application is analysis of imitation in behavioral science [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the zero-determinant strategy can be applied to cloud computing research. Zhang et al showed that a trusting party can regulate the actions of betrayers through a zero-determinant strategy, which insures the interests of honest people in the cloud computing environment [44].…”
Section: Introductionmentioning
confidence: 99%